Neuroprotective Effects of Tauroursodeoxicholic Acid Involves Vascular and Glial Changes in Retinitis Pigmentosa Model - Laura Fernández-Sánchez; Henar Albertos-Arranz; Isabel Ortuño-Lizarán; Pedro Lax; Pedro Lax; Nicolás Cuenca; Nicolás Cuenca; Nicolás Cuenca (Frontiers Media S.A., 2022)
PurposeRetinitis pigmentosa is primarily characterized by a massive photoreceptor loss. But a global retinal remodeling occurs in later stages of the disease. At that phase, glial cells and retinal vasculature are also strongly affected. The main aim of the present work is to assess if the bile acid Tauroursodeoxicholic acid (TUDCA), which has a demonstrated neuroprotective effect in numerous neurodegenerative diseases, is able to prevent glial and vascular degeneration in the P23H rat retina.MethodsHomozygous P23H (line 3) animals were injected weekly with a TUDCA (500 mg/kg, i.p.) or vehicle solution, from the postnatal day (P) 21 to P120. Sprague-Dawley rats (SD) were used as control. Retinal cross-sections and wholemounts were immunostained using different glial and vascular markers and visualized with confocal microscopy. Retinal blood vessels were stained with nicotinamide adenine dinucleotide phosphate (NADPH) diaphorase histochemistry and retinal vascular networks were drawn by hand using a camera lucida.ResultsAt P120, the photoreceptor degeneration observed in P23H rats was accompanied by a reduction in the vascular network density and complexity at the deep capillary plexus. In addition, astrocytes showed gliotic features and the outer processes of Müller cells displayed an aberrant distribution in ring-shaped structures. When treated with TUDCA, P23H rats displayed better-preserved vessels and capillary loops in the deep capillary plexus which are associated with the partial preservation of photoreceptors. TUDCA treatment also increased the number of astrocytes and reduced the presence of Müller cell process clusters in the outer retina.ConclusionThis work suggests that, besides its neuroprotective effect on photoreceptor cells, TUDCA treatment also protects from vascular and glial degeneration, a fact that encourages the use of TUDCA as a powerful therapy for neurodegenerative diseases.